Cyber-Stalking, Social Comparison, and Psychological Well-being in University Students - Agha, Fatima; Kamran, Fatima (Applied Psychology Review, 2024)
The current study aimed to investigate the relationship between cyber stalking, social comparison, and psychological well-being in university students. Correlational research design and quantitative method were used to conduct the study. It was hypothesized that there is likely a relationship between cyber stalking, social comparison, and psychological well-being. Moreover, it was also hypothesized that cyber stalking is likely to negatively predict psychological well-being in students. Data was collected online through purposive sampling technique. The study consisted of (n=150) university students. Standardized measures, Cyber Obsessional Pursuit Scale, Social Comparison Orientation Scale, and Psychological Well-being Scale, were used to collect the data. Data was analyzed using SPSS version 21. The results of correlational analysis showed highly significant correlation between all study variables. Regression analysis showed that only cyber stalking and social comparison were the significant predictors of psychological well-being in students. These results imply that authorities and respective institutions must devise psychosocial interventions to minimize the psychological disturbances in social media users by controlling cyber-crimes and to promote well-being at individual and societal level.